A Closer Look to the Evolution of Neurons in Humans and Apes Using Stem-Cell-Derived Model Systems - Schörnig, Maria; Taverna, Elena (Frontiers in Cell and Developmental Biology, 2021)
The cellular, molecular and functional comparison of neurons from closely related species is crucial in evolutionary neurobiology. The access to living tissue and post-mortem brains of humans and non-human primates is limited and the state of the tissue might not allow recapitulating important species-specific differences. Neurons derived from induced pluripotent stem cells (iPSCs) from diverse humans and non-human apes and primates offer a great tool to study species-specific neuronal phenotypes and shed light on evolutionary aspects of neurobiology. We will review herein the contribution of iPSCs-derived neuronal models to understanding species specific cell biology of neurons, their development and maturation. In addition, we will discuss the use of iPSCs for the study of ancient human traits.